ETHICS IN MEDIATION: THE ROLE OF ADVOCATES IN DISPUTE RESOLUTION - Panjaitan, Bahrumsyah; Putri Rahmayani; Selly Febriti; Andri Nurwandri (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Mediation is an alternative method of dispute resolution that is increasingly being used in the modern legal system. This process prioritizes dialogue between the disputing parties to reach an agreement without resorting to litigation. In mediation, ethics plays an important role in maintaining fairness, confidentiality and professionalism, both by the mediator and by the advocates involved. Advocates have a strategic role in mediation, namely as legal advisors who provide direction to their clients, and ensure that the mediation process runs in accordance with existing ethical principles. Advocates also function to maintain the integrity and confidentiality of information obtained during mediation, as well as ensuring that clients are not pressured into accepting detrimental agreements. In this paper, we discuss the importance of ethics in mediation, the challenges faced, and the vital role of advocates in ensuring fair and effective dispute resolution. By paying attention to ethics in mediation, it is hoped that the dispute resolution process can take place more transparently, efficiently and fairly for all parties involved.